Changes in the Expression of Mitochondrial Morphology-Related Genes during the Differentiation of Murine Embryonic Stem Cells - Jeong Eon Lee; Bong Jong Seo; Min Ji Han; Yean Ju Hong; Kwonho Hong; Hyuk Song; Jeong Woong Lee; Jeong Tae Do (Stem Cells International)
During embryonic development, cells undergo changes in gene expression, signaling pathway activation/inactivation, metabolism, and intracellular organelle structures, which are mediated by mitochondria. Mitochondria continuously switch their morphology between elongated tubular and fragmented globular via mitochondrial fusion and fission. Mitochondrial fusion is mediated by proteins encoded by Mfn1, Mfn2, and Opa1, whereas mitochondrial fission is mediated by proteins encoded by Fis1 and Dnm1L. Here, we investigated the expression patterns of mitochondria-related genes during the differentiation of mouse embryonic stem cells (ESCs). Pluripotent ESCs maintain stemness in the presence of leukemia inhibitory factor (LIF) via the JAK-STAT3 pathway but lose pluripotency and differentiate in response to the withdrawal of LIF. We analyzed the expression levels of mitochondrial fusion- and fission-related genes during the differentiation of ESCs. We hypothesized that mitochondrial fusion genes would be overexpressed while the fission genes would be downregulated during the differentiation of ESCs. Though the mitochondria exhibited an elongated morphology in ESCs differentiating in response to LIF withdrawal, only the expression of Mfn2 was increased and that of Dnm1L was decreased as expected, the other exceptions being Mfn1, Opa1, and Fis1. Next, by comparing gene expression and mitochondrial morphology, we proposed an index that could precisely represent mitochondrial changes during the differentiation of pluripotent stem cells by analyzing the expression ratios of three fusion- and two fission-related genes. Surprisingly, increased Mfn2/Dnm1L ratio was correlated with elongation of mitochondria during the differentiation of ESCs. Moreover, application of this index to other specialized cell types revealed that neural stems cells (NSCs) and mouse embryonic fibroblasts (MEFs) showed increased Mfn2/Dnm1L ratio compared to ESCs. Thus, we suggest that the Mfn2/Dnm1L ratio could reflect changes in mitochondrial morphology according to the extent of differentiation.